Dentistry Case Simulator: Amelogenesis Imperfecta (Out of Print) - Jan Hu; James Simmer; Carole Anne Murdoch-Kinch; Christine Klausner; Amy Coplen; Michael Bleed; Lynn Johnson (Association of American Medical Colleges, 2009)
Abstract Introduction Researchers at the University of Michigan School Of Dentistry, along with genetics leaders from across the country, collaborated in designing the Genetics Education in Dentistry Case Simulator to integrate genetics into existing dental/dental hygiene curricula. The program uses a combination of evidence-based teaching materials and case-based learning strategies to teach the complex decision-making skills required to care for patients with genetic diseases impacting oral health. Methods After reviewing patient histories and other information supplied in the case simulations, students work in small groups to develop a differential diagnosis and individualized treatment plan for each patient. Patient cases include video interviews, photos, radiographs, and other audiovisual media to increase the realism of the simulated experience. Results Simulation has been used in a variety of settings: at the University of Michigan with first-year dental and dental hygiene students, as well as pedodontic residents; at the University of Detroit Mercy with dental students; and at the University of Washington with residents. We saw students working through the case in many different ways. Some worked together, looking at one computer with one person typing notes. Others worked on individual computers, and some divided the assignment into sections so that they could work on it asynchronously. Many students commented on liking the group work and the real-world situation. Seeing the patient interview brought things to life for the students and was for many their favorite part. Students also commented that the program helped bring information from multiple courses together and put it into action. Discussion Sample assignments and training materials containing detailed instructions are available. Training should align closely to when an assignment is given to reduce the amount of time students have to forget how to use the program. If students are working in groups, instructors should track the students through the instructor's tool kit to make sure they get logged into the correct groups.